Consequences of hyponatraemia and hypernatraemia in children with acute diarrhoea in Bangladesh. Issue 6366 (26th February 1983) - Samadi, A R; Wahed, M A; Islam, M R; Ahmed, S M
Abstract : A total of 1330 children under 3 years of age who during 1979 had been admitted to the general ward of ICDDR, B Health Complex for diarrhoea with complications were studied retrospectively for the relation between types of dehydration, age, and nutritional state. Of the 1330 children, 276 (20.8%) were hyponatraemic, 969 (72.8%) isonatraemic, and 85 (6.4%) hypernatraemic. The incidence of hyponatraemia increased with age, while the incidence of hypernatraemia decreased with age. There was a strong relation between types of dehydration and nutritional state. The incidence of hyponatraemia was directly related to the degree of malnutrition. The case fatality rates for types of dehydration were 10.1% in hyponatraemia, 3.8% in isonatraemia, and 1.2% in hypernatraemia. These observations suggest that hyponatraemia is a serious complication of diarrhoea in Bangladesh.